MODEL PEMBELAJARAN APLIKATIF DETEKSI DINI STUNTING TERHADAP PENINGKATAN KOMPETENSI KADER ‘AISYIYAH - Awatiful Azza; Cipto Susilo (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Stunting is a significant public health problem in Jember Regency and has a long-term impact on the quality of human resources. Efforts to accelerate stunting reduction require active community involvement through strengthening the capacity of local organization-based health cadres. This study aims to analyze the application of an applied learning model for early stunting detection to improve the competence of 'Aisyiyah cadres in the community. The study used a quasi-experimental design with a one-group pretest–posttest design approach. The subjects were Aisyiyah cadres who participated in early stunting detection training. The intervention was an applied learning model that emphasized direct practice, anthropometric measurement simulations, the use of detection tools, and field mentoring. Cadre competency measurements included aspects of knowledge, attitudes, and skills before and after the intervention. Data analysis was conducted using statistical tests to determine differences in pretest and posttest scores. The results showed a significant increase in cadre competency after being given the applied learning model. There was a very significant difference between pre-test and post-test scores in 20 participants (Z = -3.195, p 0.001, r = 0.89). Improvements were seen in understanding the concept of stunting, the accuracy of anthropometric measurements, and the ability of cadres to educate mothers of toddlers. The applied learning model has proven effective in increasing cadre readiness for early detection of stunting in the community. This learning model can be used as a community-based training strategy to support programs to accelerate stunting reduction.Keywords: Early Detection; Stunting; Cadre Competency; Applied Learning Model.